THE MAIN PURPOSE FOR THE APPLICATION OF DOUBLE LAYER TIPPING BUCKET SENSORS IN RAINFALL MEASUREMENTS - Sensus Wijonarko (LIPI Press, Anggota IKAPI, 2017)
The aim of this study was to investigate the main purpose for the application of double layer tipping bucket sensors based on the existing double layer tipping bucket sensor in Tegal Climatological Station, Indonesian Agency for Meteorology, Climatology, and Geophysics. Hydraulic to electric analogy and rainfall interception models from Calder, Rutter, and Gash were used as the investigation method. The result showed that double layer tipping bucket sensors were dedicated to measure high intensity rainfalls.